Interview with Dunja Šešelja, Samuli Reijula, and Matteo Michelini (The Reasoner, 2025)
This interview discusses the use of agent-based modelling in philosophy of science with leading scholars in the field, Dunja Šešelja, Samuli Reijula, and Matteo Michelini.
Keywords: Agent-based models; computational social science.; philosophy of science